Changes in eating pattern and behavior of healthcare workers in a public hospital in light of the COVID-19 pandemic - Silva, Ana Carolina; Rodrigues, Clara (Brazilian Journal of Global Health, 2022)
RESUMO OBJETIVO: Identificar mudanças no padrão e comportamento alimentar de profissionais da saúde frente à pandemia de COVID-19. MÉTODOS: Trata-se de um estudo de campo, quantitativo, descritivo e exploratório, com amostra composta por 23 profissionais da saúde de categorias diversas atuantes nos setores de Terapia Intensiva e Urgência e Emergência. O instrumento de coleta consistiu em questionário eletrônico com questões objetivas, estruturadas em quatro partes: Informações Pessoais, Hábitos Alimentares e Questionário de Frequência Alimentar, Hábitos de Vida, Autoavaliação e Imagem Corporal. RESULTADOS: 8,7% não modificaram a alimentação pós pandemia, 13% aumentaram o consumo de refeições caseiras e alimentos naturais, 39,1% aumentaram o número de refeições fora de casa e 52,2% aumentaram o consumo de refeições prontas, fast food e delivery. Destaca-se a redução do consumo dos grupos: salada e vegetais cozidos, leguminosas e oleaginosas; manutenção do consumo dos grupos: carnes e ovos, doces e tubérculos; aumento do consumo dos grupos: laticínios, frituras e embutidos. Na categoria Atividade Física, a maior parte dos participantes (43,5%) alegam ter parado ou reduzido. Na categoria Consumo de Álcool, 52,2% tiveram seus hábitos mantidos e 39,1% alegam ter aumentado ou iniciado. 52,2% tive percepção de aumento de peso e 56,5% pioraram os hábitos alimentares durante a pandemia. CONCLUSÃO: O perfil de alimentação e de hábitos de vida que vem sendo construídos são um importante fator de risco para o desenvolvimento de obesidade, doenças cardíacas, diabetes e hipertensão arterial, todos relacionados a complicações do COVID-19. DESCRITORES: Hábito alimentar, Comportamento alimentar, COVID-19, Pandemia, Profissional da saúde. ABSTRACT OBJECTIVE: Identify changes in the eating pattern and behavior of health professionals faced with the COVID-19 pandemic. METHODS: This is a field study, quantitative, descriptive, and exploratory, with a sample composed of 23 health professionals from different categories working in the Intensive Care and Emergency sector. The collection instrument consisted of an electronic questionnaire with objective questions, structured in four parts: Personal Information, Eating Habits and Food Frequency Questionnaire, Life Habits, Self-Assessment and Body Image. RESULTS: In total, 8.7% of the participants did not change their diet after the pandemic began, 13% reported increased consumption of homemade meals and natural foods, 39.1% increased the number of meals eaten outside the home, and 52.2% increased their consumption of ready meals, fast food, and delivery. The following groups stand out: reduced consumption of salad and cooked vegetables, legumes and oilseeds; maintenance in the consumption of meat and eggs, sweets, and tubers; and increased consumption of dairy products, fried foods, and sausages. In the Physical Activity category, the majority of participants (43.5%) claim to have stopped or reduced their practice. In the Alcohol Consumption category, 52.2% reported maintaining their habits, and 39.1% claimed to have increased or started alcohol consumption. In addition, 52.2% perceived weight gain and 56.5% presented worsening eating habits during the pandemic. CONCLUSION: The dietary profile and lifestyle habits being established are an important risk factor for the development of obesity, heart disease, diabetes, and high blood pressure, all of which are related to complications from COVID-19. DESCRIPTORS: Eating habits, Eating behavior, COVID-19, Pandemic, Health professional.